PERAN GURU PPKn DALAM MEMBUDAYAKAN GERAKAN LITERASI SEKOLAH PADA PESERTA DIDIK DI SMPE NEGERI 2 KOTA TERNATE (STUDI KASUS DI KELAS VIII) - R. Usia, Tri Enadha; Hasmawati, Hasmawati; Sergie, Misrina (Jurnal GeoCivic, 2023)
This research was motivated by students' lack of interest in reading and awareness of the importance of literacy and literacy only because it was requested or ordered by the teacher. The aims of this research were 1) to find out the role of Civics teachers in cultivating the literacy movement in students of SMP Negeri 2 Kota Ternate, 2) knowing the factors that support and hinder the school literacy movement in students. This research is a qualitative descriptive study using the case study method and the subjects of the research are the principal, Deputy Head of Student Affairs, Class VIII PPKn Teachers and Grade VIII students. Data collection techniques used are observation, interviews and documentation. Data analysis techniques using data reduction, data presentation and conclusion/verification. The results of this study indicate that (1) PPKn teachers always give firm encouragement to students to be literate, asking students to read and make summaries by carrying out literacy 15 habits in class for each subject (guided literacy), asking students to read first at home before going to school (cultural literacy), Encourage students to take advantage of their free time so that they are always in class to read ( literacy continuity ), as well as in reading areas that have been provided by the school. (2) There are supporting and inhibiting factors for the School Literacy Movement for students of SMP Negeri 2 Kota Ternate, the supporting factors are that the facilities for literacy are available, the implementation of literacy has been carried out by the teacher through habituation of reading and writing literacy to students, there are books in every reading corner in the classroom and in the library. Meanwhile, the inhibiting factor is the lack of motivation of students to be literate and only literate when instructed by the teacher, and there is one area of literacy that is rarely used.Keywords: PPKn Teachers, GLS Culture, Students